2022
DOI: 10.1007/s10668-022-02568-0
|View full text |Cite
|
Sign up to set email alerts
|

The nexus between traditional foraging and its sustainability: a qualitative assessment among a few selected Eurasian case studies

Abstract: Plant foraging is an important human ecological phenomenon being studied by a number of contemporary ethnobiologists as well as by a few social anthropologists among rural communities and, more recently, in urban environments. The sustainability dimension of foraging is, however, largely unexplored. We analyse a few case studies from recent field research and qualitatively assess both the environmental and social sustainability of diverse patterns of traditional foraging practices in three distinct human ecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…Literature detailing overharvest threats to plants' conservation notes that these are fuelled by a commercial demand beyond the local market (Ghimire et al, 2005; Law & Salik, 2005; Ouarghidi et al, 2017). Furthermore, if foragers are in a socio‐economically vulnerable situation, existing considerations of plant availability can be overridden by high market pressures, leading to overharvest (Aziz et al, 2022). Sustainable large‐scale commercial foraging, spanning multiple geographical scales and sites and where foragers' are not also the final resource users, requires a different definition and assessment that is not necessarily based on the reciprocal individual relationships of foragers with the harvested biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…Literature detailing overharvest threats to plants' conservation notes that these are fuelled by a commercial demand beyond the local market (Ghimire et al, 2005; Law & Salik, 2005; Ouarghidi et al, 2017). Furthermore, if foragers are in a socio‐economically vulnerable situation, existing considerations of plant availability can be overridden by high market pressures, leading to overharvest (Aziz et al, 2022). Sustainable large‐scale commercial foraging, spanning multiple geographical scales and sites and where foragers' are not also the final resource users, requires a different definition and assessment that is not necessarily based on the reciprocal individual relationships of foragers with the harvested biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…This clearly shows how significant is the role of wild plants in the resilience of people under conflict conditions. The sustainability of wild plant use is another crucial aspect that has been affected in recent years; local people reported that the abundance of several species has significantly decreased [15].…”
Section: Syriamentioning
confidence: 99%
“…Vaccinium myrtillus is largely available in (Western) Ukraine, yet its productivity depends on the year and on the intensity of the previous harvest. In some areas of Ukraine, we observed an over-harvesting status of berries due to the crucial importance of this product for local economies of some Carpathian villages [15]. Corylus avellana is widely used as a building material for fences, decorations, and garden braces.…”
Section: Economic Value Of the Reported Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to disruptions and distrust in food supply chains, consumers have gained interest in alternative ways forms of food procurement, including self-sufficiency and food foraging [7]. These alternative forms of food procurement allow consumers to avoid panic buying incidences [26], somewhat mitigate food insecurity, e.g., the use of food pantries and food stamps, and are in line with consumer trends in terms of healthy eating and gardening [34,35]. Amidst this background, the following hypotheses are proposed: Hypothesis 2a (H2a).…”
Section: Food-related Covid-19 Concernsmentioning
confidence: 99%